Flow resistance in open channel flows over triangular element simulating dunes - Rusli, Alwyn (2017)
The increasing importance of artificial waterways from the past as the natural artery to promote trade across the island to the current context for rainwater collection requires special attention to ensure performance and stability in protecting lives and great economic value. As the water catchment area will increase in size to 90% of total area, it is of great importance to ensure sustainable waterway network to provide consistent recreational and economic activities in Singapore. Dunes, one of the naturally-occurring large-scale bedforms, substantially increase the bed resistance affecting the flows in waterways. Limitation of past studies not accommodating the effect of regular, artificial dunes on artificial waterways over various water depth combined with the lack of progress in the studies has brought up this study. The present study examines the effect of various flow parameters on fabricated dunes through experimental study using fabricated dunes. Several approaches to measure the overall friction factor were used, the first two empirical approaches based on energy and momentum perspectives and the latter on the experimentally-derived equation. A total of 3 dune models with 4 different slopes each, and 7 various flow depths for each slope, were evaluated to develop qualitative insights of dune flow problems. Results from the three approaches present consistent downward trend of total friction factor because of flow discharge fluctuation, which in turn fluctuate water levels. Typically, the decreasing rate of change of the friction factor is of greater value when the water height to dune height ratio is below 2. Initially, skin resistance dominates the overall friction factor when the flow discharge is low. However, wake resistance is of greater importance as flow discharge gets larger denoting the effect of flow separation. The larger the ratio, the lower will be the overall friction factor. Drag force imposed upon the flow by the same dune model over different slopes and various flow discharges is of similar values.